Facing Water Stress in a Changing Climate: A Case Study of Drought Risk Analysis Under Future Climate Projections in the Xi River Basin, China - Wang, Keyi; Niu, Jun; Li, Tiejian; Zhou, Yang (Frontiers in Earth Science, 2020)
China, with its fragile environment and ecosystems, is vulnerable to climate change. Continuous changes in climatic conditions have altered precipitation patterns in most regions of China. Droughts become more frequent and severe in the Xi River basin in South China. It is expected that rapid urbanization and climate change will continue to aggravate water stress in this region. There is an urgent need to develop sustainable water management strategies in face of growing water demand and changing water availability. Projection of future climate change impacts on drought conditions has thus become imperative to support improved decision-making in sustainable water management. In this study, we assessed the risk of extreme droughts under future climate projections in the Xi River basin. The Variable Infiltration Capacity (VIC) model was applied to simulate the hydrological processes of the basin under a multitude of future climate scenarios from CMIP5. Based on the precipitation and runoff series obtained from the VIC model, a comprehensive analysis with respect to the major characteristics of meteorological and hydrological droughts had been carried out. This study is of practical and theoretical importance to both policymakers and scholars. First, this study may be a readily available reference work for policymakers when taking consideration of building drought mitigation plans into future water management practices. Second, the findings in this study may provide some valuable insights into the inherent connection between climatic and hydrological changes under a changing climate. Recognition of the connection and interrelation may contribute to the improvement of climatic and hydrological models in practices.